ANALISIS INVESTASI, PENGELUARAN PEMERINTAH DAN PERTUMBUHAN EKONOMI TERHADAP KESEMPATAN KERJA DI PROPINSI NUSA TENGGARA BARAT - Endang Astuti, Muammil Sun’an, (IQTISHODUNA, 2008)
Employment or unemployment indeed is a global problem faced by almost all countries in the world, developing and developed industrial countries are facing same problem. The intensity of problem might be different from among the countries due to difference influence factors, such as economic growth, investment or government expenditure directly influence on creating employment. High economic growth rate and investment will increase employment. While changes in government expenditures is too much depended on proportion or budget allocation for development finance. Research findings in the province of Nusa Tenggara Barat indicate that economic growth and investment influence on the increasing employment. Agricultural, industrial and services sectors bring positive influence through increasing investment values on creating employment, while economic growth doesn’t influence on employment in agricultural sector, instead its influence on industrial and services sectors. Expansive fiscal policy brings negative influence on employment in industrial sector, but however, on the other side it has positive influence on employment in services sector. Employment in districts / towns in the province of Nusa Tenggara Barat influenced by economic growth and government expenditure.